Efecto de la enmienda biocarbon+biol y sio2 en un suelo franco arenoso sobre el desarrollo vegetativo de musa sp. - Sanchez Pilcorema, Stalin Enrique (Machala : Universidad Técnica de Machala, 2020)
Banana production is one of the main export crops worldwide, contributing with a high economic level to the country with the generation of direct or indirect sources of employment for many families. In Ecuador and mainly within the province of El Oro they contribute approximately 42% of banana production thanks to the fertility of their soils and optimal environmental conditions for the production of a unique product worldwide. The main disadvantage of the crop is the misuse of chemicals that cause contamination of the water, the environment and mainly the degradation of the soil, which is the most important factor for production. At present, banana soils and the environment are affected by the misuse of agrochemicals, causing physical and chemical problems, lowering production yields due to the accumulation of heavy metals that come in the formulations of agrochemicals. That is why the focus of this research was born with the purpose of counteracting the degradation of the soil and pollution of the environment using a biochar from cocoa shells, a raw material that is used because it absorbs the heavy metals present in the soil and increases the percentage of efficient microorganisms, also increasing the productivity of the cultures, in combination with a biol that adheres to Trichoderma spp, used for its ability to degrade pathogenic fungi; requiring humidity for its establishment and reproduction in the soil, and being able to control diseases to the crop and silicon oxide with 30% organic matter that provides its benefits at the edaphic and plant level, also delaying the increase of black sigatoka. The research was carried out in the banana farm "San Carlos" belonging to the El Guabo canton, in the province of El Oro, the treatments were applied with the purpose of comparing the effects of cocoa biochar in increasing doses (10g, 20g, 30g), in combination with 100 g of SiO2 and three levels of biol (100ml, 150ml, 250ml), each one at 10 repetitions. The results reflected in this investigation in the height of the child, the treatment that showed the greatest growth was T1 with a height of 217.80 cm compared to T0 with a height of 195.40 cm; in the thickness of the pseudostem, T1 showed a greater circumference growth of 57.60 cm in contrast to the control treatment T0, which showed a thickness of 52.10 cm; the number of leaves of the son on T2 and T0 showed homogeneity in their results with 11 leaves each treatment, while in T1 and T3 they presented 8 and 9 leaves per plant; the weight of bunches obtained in T1 and T3 was 23.70 kg, with a great noticeable difference in the control treatment T0, which was obtained at a weight of 17.40 kg; treatments T1, T3 and T0 showed an equality in the number of hands in the bunches, unlike T2, which was where a greater number of hands was obtained; In the foliar emission of the mother plant, treatments T1 and T2 presented a greater number of leaves (9 leaves) while in the control treatment T0 we reached the harvest with 6 leaves. The effect of the treatments on the development of the plants was noticeable compared to the control.
La producción de banano es uno de los principales cultivos de exportación a nivel mundial, contribuyendo con un alto nivel económico al país con la generación de fuentes de empleos directa o indirectamente para muchas familias. En Ecuador y principalmente dentro de la provincia de El Oro aportan aproximadamente con el 42% de la producción de banano gracias a la fertilidad de sus suelos y condiciones ambientales óptimas para la producción de un producto único a nivel mundial. La principal desventaja que presenta el cultivo, es el mal uso de los productos químicos que causan la contaminación del agua, medio ambiente y principalmente la degradación de los suelos que es el factor más importante para la producción. En la actualidad los suelos bananeros y el ambiente son afectados por el mal uso de agroquímicos, causando problemas físicos y químicos, bajando los rendimientos de producción por la acumulación de los metales pesados que vienen en las formulaciones de los agroquímicos. Es por esto que el enfoque de esta investigación, nace con el propósito de contrarrestar la degradación del suelo y contaminación del medio ambiente utilizando un biocarbón de cáscaras de cacao, materia prima que es utilizada porque absorbe de los metales pesados presentes en el suelo e incrementa el porcentaje de microorganismos eficientes, aumentando también la productividad de los cultivos, en combinación de un biol que se le adhiere trichoderma spp, utilizado por su capacidad de degradar los hongos patógenos; requiriendo humedad para su establecimiento y reproducción en el suelo, y poder controlar las enfermedades al cultivo y óxido de silicio con un 30% de materia orgánica que aporta sus beneficios a nivel edáfico y vegetal retardando también el incremento de la sigatoka negra. La investigación se realizó en la finca bananera “San Carlos” perteneciente al cantón El Guabo, de la provincia de El Oro, los tratamientos se aplicaron con el propósito de comparar los efectos del biocarbón de cacao en dosis creciente (10g, 20g, 30g), en combinación con 100 g de SiO2 y tres niveles de biol (100ml, 150ml, 250ml), cada uno a 10 repeticiones. Los resultados reflejados en esta investigación en la altura del hijo el tratamiento que mostró un crecimiento mayor fue el T1 con una altura de 217,80 cm en comparación con T0 con una altura de 195,40 cm; en el grosor del pseudotallo el T1 mostró un mayor crecimiento de circunferencia de 57,60 cm a diferencia del tratamiento control T0 que mostró un grosor de 52,10 cm; el número de hojas del hijo el T2 y T0 mostraron una homogeneidad en sus resultados con 11 hojas cada tratamiento, mientras que en los T1 y T3 presentó 8 y 9 hojas por planta; el peso de racimos obtenido en el T1 y T3 fue de 23,70 kg, con una gran diferencia notoria en el tratamiento control T0 que se obtuvo a un peso de 17,40 kg; los tratamientos T1, T3 y T0 mostraron una igualdad en el número de manos del racimos, a diferencia del T2 que fue donde se obtuvo un número mayor de manos; en la emisión foliar de la planta madre los tratamientos T1 y T2 presentaron un mayor número de hojas (9 hojas) mientras que en el tratamiento control T0 llegamos a la cosecha con 6 hojas. El efecto de los tratamientos sobre el desarrollo de las plantas fue notorio frente al testigo.
Keywords: BANANO; CACAO; PSEUDOTALLO; BIOCARBON